Microstructural engineering of flexible and broadband microwave absorption films with hierarchical superstructures derived from bimetallic metal-organic framework. (30th June 2021) - Xu, Xueqing; Ran, Feitian; Fan, Zhimin; Cheng, Zhongjun; Xie, Zhimin; Lv, Tong; Liu, Yuyan
Abstract: The potential electromagnetic interference in rapid emerging of smart and wearable electronics has significantly stimulated the exploration of microwave absorption (MA) materials. Nevertheless, the fabrication of flexible and broadband microwave absorbers remains a great challenge. Herein, the flexible MA films have been fabricated through constructing bimetallic ZIFs derived hierarchical superstructures onto carbon-fiber cloth and subsequent polymer encapsulation. By controlling the synthesis condition, three types of hierarchical CoZn-ZIF superstructures with different morphology of building block on cotton-fiber (CC/ZIFs) have been successfully yielded. After subsequently two-step morphology-preserved thermal transformation process, the derived superstructures are comprised of hollow Co3 O4 nanosphere embedded in carbon frameworks on flexible carbon-fiber cloth (CC/ZIFs-300). The superstructures coupled with carbon-fiber cloth have effectively promoted electron transportation, conductive loss, polarization loss, multi-scattering, and impedance matching. As expected, the flexible MA films exhibit ideal MA performances, and the largest effective absorption bandwidth can reach as 11.6 GHz. This work provides a novel concept for further design of flexible MA materials. Graphical abstract: Image 1 Highlights: The flexible microwave absorption films have been fabricated from bimetallic ZIFs on cotton-fiber cloth. The superstructures coupled with carbon-fiber cloth have effectively promoted dielectric loss capacity. Hollow Co3 O4  particles and carbon framework could improve the dipole polarization loss and impedance matching. The largest effective absorption bandwidth can reach as 11.6 GHz.